Distance Learning: The Impact on Teaching and Learning Process - Sujariati Sujariati; Risman Wanci (AL-ISHLAH: Jurnal Pendidikan, 2023)
The Covid-19 pandemic forced the teaching and learning system by distance. The purpose of this study to investigate the struggle and challenges were faced by students and teachers to ensure the effects on students’ learning achievement before and during distance learning. This research applied a descriptive qualitative method with some questionnaires that dealt with students’ perceptions of using distance learning. Moreover, this research applied interviews to compile the previous data from the questionnaire. The results showed that distance learning has impacts and effects. The impacts and effects were mostly negative, shown by the responses of students’ perception of using distance learning in questionnaires and interviews; namely, the networking was not good, the teaching was not clear, and it was difficult to understand the materials. On the other side, the teacher’s responses showed; that the learning process has not been completed, sometime the network is not good, the students were not disciplined either entering class or submitting assignments, and the students had a decline in motivation, interest, and enthusiasm in learning. For the effects, the students’ value of learning achievement declined significantly from good to fair. The data was taken from evaluation scoring at the end semester. In conclusion, there are a great deal of factors to consider in order to ensure a smooth learning experience when completing coursework online.